Komposisi Jenis Katak (Anura) di Taman Nasional Gunung Palung, Kalimantan Barat - Tri Rima Setyawati, Margie Surahman Junardi (Jurnal Protobiont, 2018)
The population of frogs in Gunung Palung National Park is indicating a decline due to habitat degradation and hunting. The aim of this research is to determine the species of Anura at five habitat with using Complete Species Inventories (CSI) method combined with Time Search method. The study found 27 Anura species included in 6 families namely Megophryidae (Megophrys nasuta), Bufonidae (Ansonia sp. and A. spinulifer), Microhylidae (Microhyla malang, and M. perparva), Ranidae (Meristogenys jerboa, M. whiteheadi and Staurois guttatus), Dicroglossidae (Limnonectes leporinus and L. kuhlii), and Rhacophoridae (Kurixalus appendiculatus, Rhacophorus sp., R. gauni, and R. pardalis).